Hedonic and Proximate Evaluation of Avocado-Banana Uli Puree in Nutrition Program Management - Lubis, Rahmi Amelia; Febrianty, Widya; Demitri, Athira (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Local food innovation plays a significant role in improving community nutrition by providing nutrient-rich, culturally acceptable products. Avocado (Persea americana) and Banana Uli (Musa x paradisiaca L. AAB) are potential local ingredients that can be developed into functional food for nutrition programs. This study aimed to evaluate the hedonic acceptance and proximate composition of dry sponge cake fortified with avocado flour and banana uli puree to support nutrition program management. A completely randomized design with three formulations was applied: F1 (10 g avocado flour + 15 g banana uli puree), F2 (15 g + 10 g), and F3 (20 g + 5 g). Hedonic tests on color, aroma, taste, and texture were conducted by trained panelists, and proximate analysis included carbohydrate, protein, fat, potassium, moisture, and ash content. Results indicated that formulation F1 achieved the highest hedonic scores for taste (4.08 ± 0.12) and texture (4.36 ± 0.15), with neutral brown color and neutral avocado aroma. Proximate analysis of F1 showed 71.2 g carbohydrates, 10.5 g protein, 1.8 g fat, 159.9 mg potassium, 7.26% moisture, and 0.69% ash per 100 g. F1 was identified as the optimal formulation due to its sensory acceptance and nutritional quality. This study demonstrates that developing dry sponge cake using local ingredients can enhance community nutrition while supporting the implementation of nutrition program management through functional and culturally appropriate foods.